Macrófitas aquáticas do reservatório Luís Eduardo Magalhães - Lajeado - Tocantins : biomassa, composição da comunidade e riqueza de espécies. - Lolis, Solange de Fátima (2008)
The objective of the present study was to evaluate the composition and richness of the water macrophyte community of the Lajeado Reservoir and the biomass of two species. Samples were collected at five different locations from March/2005 through February/2006. This thesis was divided into three chapters. The first, entitled "Community composition and water macrophyte species distribution in the Luis Eduardo Magalhães Reservoir, Lajeado - Tocantins, Brazil", reports a twelve-month evaluation of the water macrophyte community distribution, richness and beta 1 diversity for which bi-monthly samplings were carried out. In the second chapter, entitled "Spatial-temporal variation of the water macrophyte community in two periods of time in the Luis Eduardo Magalhães Reservoir - Tocantins - Brazil", the spatial and temporal variation of the water macrophyte community in relation to some abiotic variables was analyzed. The third chapter, entitled "Temporal variation in the biomass of Oxycaryum cubense (Poepp. & Kunth) Lye (Cyperaceae) and Salvinia auriculata Aubl. (Salviniaceae) in the Lajeado Reservoir, Tocantins, Brazil", evaluated the spatial-temporal variation in the biomass of those two species and some abiotic variables.